Growth of Foreign Assistance and its Impact on Agriculture - Lele, Uma (International Food Policy Research Institute, 1987)
Justifications of foreign aid may be classified into two basic categories. The first claims that aid is a form of progressive international taxation in which income is redistributed from rich to poor countries in much the same way as among income classes within nations. Recipients of aid preferthis justification, but it has not been broadly accepted in donor countries, and in recent years may have lost ground. Public opinion surveys in countries belonging to the Organization for Economic Cooperation and Development (OECD) indicate that while 79 percent of those interviewed in the United States approved of emergency aid, only 49 percent supported development assistance (OECD 1984a). The second justification is that aid is needed to correct international market failures.